The jurists : a critical history - Gordley, James (Oxford : Oxford University Press, 2014)
Current Western law has been shaped by the work of successive schools of jurists throughout the ages. From ancient Rome to the present, this book describes their work in their historical context and their influence on later schools.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on November 5, 2013).
Keywords: Law -- Europe -- History; Law -- Europe -- Interpretation and construction -- History; Lawyers -- Europe -- History